Efektivitas Media Pembelajaran LKPD ditinjau dari Minat Belajar Matematika Peserta Didik Kelas IX SMPN 3 Lingsar Tahun Ajaran 2024/2025 - Lu'luilmaknun, Ulfa; Salsabila, Nilza Humaira; Janah, Baiq Liatul Ukmatul; Januarsi, Putri (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the effectiveness of the Student Worksheet (LKPD) learning media in increasing the mathematics learning interest of ninth-grade students at SMPN 3 Lingsar in the 2024/2025 academic year. The research employed a pre-experimental method with a one-group pretest-posttest design. A total of 20 students were selected using purposive sampling. The research instrument was a learning interest questionnaire administered before and after learning activities using LKPD. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, and paired t-test. The results showed that the data were normally distributed and homogeneous. The paired t-test result indicated a p-value of 6.94 × 10⁻¹⁰ (< 0.05) with a t-value of 11.315. This finding demonstrates a significant difference between students' learning interest scores before and after using LKPD. Therefore, it can be concluded that the LKPD learning media is effective in increasing students’ interest in learning mathematics. This finding is expected to serve as a reference for teachers in selecting appropriate learning media to improve students' learning interest in the classroom.